PENGARUH KUALITAS PELAYANAN, SANKSI PAJAK DAN KONDISI KEUANGAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - DWI RATNA YANTI, WIDIA (Jurnal Akuntansi AKUNESA, 2018)
This study was conducted to determine the effect of service quality, tax sanction, and financial condition of the taxpayer on the compliance of the motor vehicle taxpayer. This research uses quantitative approach with primary data obtained from questionnaires distribution and secondary data obtained from East Java Province Revenue Service in the form of data of target development and realization of motor vehicle tax and motor vehicle data report that has not done research again. Samples taken as many as 100 motor vehicle taxpayers registered at the office with SAMSAT Mojokerto. This study used multiple linear regression analysis technique using SPSS version 21 program. The results of this study indicate that the service quality, tax sanction, and financial condition of the taxpayer have a positive effect on the taxpayer compliance of motor vehicles.